Pengaruh Gaya Kepemimpinan Transformasional Kepala Sekolah dan Motivasi Kerja Terhadap Disiplin Kerja Guru Madrasah Aliyah Negeri di Wilayah Jakarta Selatan - Wibowo, Heru (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2021)
This research aims to recognize the influence of the transformational school principal style leadership and working’s motivation to the teachers’ of senior Islamic high school state in the South Jakarta which consists of 143 people. Because of the large samples which consist of 105 people, the writer uses Slovin formula in this research and the way of data taken is based on school unit proportionally. The research variable includes the transformational school principal style leadership (X1), Working’s motivation (X2) and the discipline of teachers’ dedication (X3). Then the writer uses questionnaire to get the data. This research hypothesis is (1) there is a direct influence, the transformational school principal style leadership to the discipline of teachers’ dedication, (2) there is a direct influence between working’s motivation and the discipline of teachers’ dedication, (3) there is direct influence between the transformational school principal style leadership and working’s motivation. The each hypothesis 1,2,3 are tested by simple regression and partial correlation. However, the writer uses the analysis for the next. The writer uses the survey as his method with the data analysis inferentially. The research result which is found is the first research result concludes that there is a positive influence between the transformational school principal style leadership (X1) and the discipline of teachers’ dedication (X3), with the coefficient iv correlation is 0.639 , on α = 0.05, and the determination coefficient is 0.408. It shows that 40.8 % of the discipline of teachers’ dedication is strengthened by the transformational school principal style leadership with coefficient channel 0.344 and correlation is 0.639. The result of second hypothesis concludes that there is a positive influence between working motivation (X2) and the discipline of teachers’ dedication (X3) with the coefficient correlation is 0.529 on α = 0.05, the determination coefficient is 0.279. it shows that 27.9 % is strengthened by the working’s motivation with coefficient channel 0.529 and the correlation is 0.529. the result of third hypothesis concludes that there is a positive influence between independent variable of the transformational school principal style leadership (X1) and working’s motivation (X3) with the coefficient correlation is 0.656 the determination coefficient is 0.430. it shows that 43.0 % of the discipline of teachers’ dedication is strengthened by the transformational school principal style leadership and the working teachers’ motivation with coefficient channel is 0.656 and the correlation is 0.185. This research recommends all the school principals to improve the transformational style leadership ability in order to do their policies and to improve the teachers of Islamic senior high school state ’ motivation in the south Jakarta in order to create the good and discipline work